Enhancing Students’ Understanding of Akidah and Akhlak through STAD Cooperative Learning Model at MIS Ntonggu, Pali Belo, Bima, NTB: A Classroom Action Research - Wahyudin; Siti Lauhil Bariah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) investigates the effectiveness of the STAD (Student Teams-Achievement Divisions) cooperative learning model in enhancing students’ understanding of Akidah and Akhlak at MIS Ntonggu, Pali Belo, Bima, NTB. The study focuses on improving students’ cognitive and affective aspects by implementing cooperative learning strategies that emphasize teamwork and shared responsibility in mastering religious and moral education. The research was conducted with 5th-grade students, aiming to assess the impact of cooperative learning on their comprehension of key Islamic principles and their ability to apply these principles in their daily lives. The research was carried out in two cycles, each consisting of planning, action, observation, and reflection. During each cycle, the STAD model was implemented, where students were divided into small groups and given specific tasks to complete together. Group performance was assessed based on individual and team achievements. Data were collected through pre- and post-tests, classroom observations, and student feedback to measure the effectiveness of the STAD model in improving understanding and application of Akidah and Akhlak. The findings suggest that the STAD cooperative learning model significantly improved students’ understanding of Akidah and Akhlak, as well as their ability to apply Islamic values in their behavior. The collaborative nature of STAD increased student engagement, motivation, and social interaction, fostering a positive learning environment. Furthermore, students demonstrated improved teamwork and responsibility, which are essential for their personal and social development. This research highlights the potential of cooperative learning models like STAD in enhancing religious education and character development in elementary schools.